Grassland specialist birds in a managed habitat of north-east Bangladesh (Dhaka University Journal of Biological Sciences, 2017)
A seven‐month spanned study from November, 2015 to May, 2016 was carried out to investigate the status and fluctuation of grassland dependent birds in a Saccharum‐Imperata patch locating in the northeastern Bangladesh under ownership of a tea‐garden; applying line transects with direct observation and diversity index. A total of 2586 individuals of 110 species was observed, grassland specialists constituted 829 (32%) individuals from 39 (35%) species. Only seven non‐passerine specialists were observed against 32 passerine specialists whereas 19 being resident and 20 wintering species. Of the grassland specialists, 31% turned out as few, 33% fairly common, 21% common and 15% very common. Insectivores and seed‐eaters were dominant feeding guilds over scavengers and omnivores at the site yielding nine categories. Specialists scored the highest value in Shannon’s Index for November (H′sp.nov = 2.81) followed by a steady decline throughout the study period. The largest winter congregation of Yellow‐breasted Bunting and Common Rosefinch in Bangladesh was observed and sighting of Black‐headed Bunting was the fourth national record. The site was found to be supporting breeding population of Golden‐headed Cisticola so far only known to country’s inventory. Despite once supporting about 10 extirpated avian species and still being diverse, adequate information on grasslands is still wanting in Bangladesh.Dhaka Univ. J. Biol. Sci. 26(2): 175-187, 2017 (July)